El uso de la guitarra como herramienta de estimulación de la memoria en los estudiantes de las escuelas no formales de las artes de la casa de la cultura ecuatoriana Núcleo de Bolívar, durante el período mayo – septiembre 2023 - Gaibor López, Ibeth Zoraida (2023)
Learning the guitar is not limited solely to the acquisition of musical skills, but it can also generate positive effects on memory through cognitive stimulation, motor coordination, repetitive and strengthened practice, emotional connection, and motivation. In this context, the present research aims to describe and determine how the use of the guitar can influence memory stimulation in students from non-formal arts schools at the "Casa de la Cultura Ecuatoriana Núcleo de Bolívar." The choice of this research topic is based on the deficiencies identified in students during their pre-professional practices. These practices revealed a lack of study habits and the scarce implementation of methods that promote memory stimulation in the teaching-learning process. These limitations, in turn, negatively impact students' academic performance. To carry out this study, a descriptive qualitative approach was adopted. Information was collected through interviews conducted with teachers, with the purpose of subsequently analyzing and interpreting the results. Finally, it was concluded that the findings obtained have the potential to impact the planning of educational programs that seek to incorporate musical components to enhance students' cognitive capacity. Additionally, they could stimulate a greater interest in music and artistic education in general, thus contributing to the comprehensive development of students in the artistic and cultural educational field.